MAKNA DAN PERUBAHAN RELASI GENDER BAGI PEREMPUAN PEKERJA DADAKAN DI MASA PANDEMI COVID-19 - Ditha Aziezah Setiyono; Johanna Debora Imelda (Jurnal Sosiologi Reflektif, 2021)
2020 is a historic year due to the outbreak of the Covid-19 virus. As a result, people are forced to adapt to a new normal situation, which changes their daily lives order. In this condition, women are experiencing a double burden, including when men, as 'breadwinners', has experiencing the termination of employment (PHK) or decreasing in his income. There are various ways that women do for supporting their children and family needs. Such as being an unexpected worker. This study aims to provide an explanation on the meaning of being an unepected worker and gender relation changes using Bourdieu perspective. The research method employed is descriptive qualitative, using a case study. Data are collected through in-depth interviews, observation, and documentation. The results showed that the meaning of becoming an unexpected worker and  the process of gender relations changes cannot be separated from the habitus of women. Work has economic and non-economic meaning when workers become impromptu workers. In the context of changing gender relations, the higher level of women education, the more parallel the gender relations are formed. Vice versa, the lower of their educations, the more domination of men in a gender relation. Tahun 2020 menjadi tahun bersejarah karena merebaknya virus Covid-19, akibatnya masyarakat mengubah tata cara kehidupan sehari-hari. Dalam kondisi ini, perempuan menjadi pihak yang harus bekerja ekstra, termasuk saat laki-laki sebagai 'income earner' mengalami Pemutusan Hubungan Kerja (PHK) atau pengurangan pendapatan. Berbagai cara dilakukan perempuan untuk anak dan kelangsungan keluarga, salah satunya dengan menjadi perempuan pekerja dadakan. Penelitian ini bertujuan untuk memberi gambaran makna menjadi pekerja dadakan dan perubahan relasi gender yang terjadi denga menggunakan teori sosial Bourdeui. Metode penelitian yang digunakan penelitian kualitatif deskriptif dengan jenis studi kasus. Pengumpulan data dilakukan melalui wawancara mendalam, observasi dan dokumentasi. Hasil penelitian menunjukan makna menjadi pekerja dadakan dan perubahan relasi gender tersebut tidak lepas dari habitus perempuan. Terdapat makna ekonomi dan non-ekonomi saat perempuan menjadi pekerja dadakan. Dalam konteks perubahan relasi gender semakin tinggi tingkat pendidikan semakin sejajar relasi gender yang terbentuk. Begitu pula sebaliknya, semakin rendah tingkat pendidikan semakin perempuan didominasi oleh laki-laki dalam sebuah relasi gender.